THE BIOMOLECULAR CHARACTERISTICS OF ANGIOTENSIN II TYPE 1 RECEPTORS AS PARAMETERS IN KIDNEY FIBROSIS: A BIOINFORMATICS ANALYSIS - Evi Lusiana; Irfannuddin Irfannuddin (Majalah Kedokteran Sriwijaya, 2022)
AGTR1 is a modulator of angiotensin II-induced signal transduction. This article aims to examine the biomolecular characteristics of AGTR1 and the role of AGTR1 in the renal fibrosis pathway in Rattus norvegicus rats. The gene ID NC 051352.1 and protein ID NP 112271.2 for AGTR1 were retrieved from the National Center for Biotechnology Information's website. The 'NCBI' website has details on AGTR1's structure, location, and expression. Protease prediction using 'PEPTIDE CUTTER'; glycosylation index prediction using NETNGLYC; and target protein location evaluated on the 'TARGETP' homepage. AGTR1 in Rattus norvegicus is located on chromosome 17p12, This protein has a stability score of 34.48. The aliphatic index was 114.62. AGTR1 is found inside, outside, and on the transmembrane, as determined by the THMM. Only 21 enzymes were predicted to be capable of cleaving the AGTR1 protein, out of a total of 37 protease. AGTR1 protein has four glycosylated amino acid sequences. AGTR1 protein is primarily at other location 0.850, secretory pathway (0.590), and a little amount in mitochondria (0.018AGTR1/AT1R is a marker for renal fibrosis in the renin angiotensin system, which can lead in vasoconstriction, inflammation, fibrosis, sodium retention, and water retention. The AGTR1 protein's molecular feature is a determinant in the progression of renal fibrosis, revealed to a bioinformatics study.